Anti‐phosphoenolpyruvate carboxykinase 2 antibody in patients with autoimmune hepatitis. Issue 9 (27th January 2014) - Kanno, Yukiko; Watanabe, Hiroshi; Takahashi, Atsushi; Abe, Kazumichi; Ohira, Hiromasa
<x xml:space="preserve">Abstract</x> Aim To identify a novel autoantibody specific to autoimmune hepatitis (AIH) and to evaluate its clinical significance. Methods Non‐nuclear component protein extracted from normal human liver cell CyrohNHpes cultures that reacted with sera from AIH patients on a western blot was identified as an antigenic protein and subjected to N‐terminal amino acid analysis to identify phosphoenolpyruvate carboxykinase 2 (PCK2). Enzyme‐linked immunoassay (ELISA) for anti‐PCK2 antibody was conducted on sera samples from patients with AIH (n = 42), primary biliary cirrhosis (PBC; n = 48), non‐alcoholic steatohepatitis (NASH, n = 41), chronic hepatitis C (CHC, n = 20), drug‐induced liver injury (DILI, n = 10), systemic lupus erythematosus (SLE, n = 16) and on sera samples from healthy volunteers (n = 30). Clinical findings were compared for AIH patients testing positive and negative for anti‐PCK2 antibody. Results ELISA findings showed that mean anti‐PCK2 antibody titer in sera from AIH patients was significantly higher than in PBC, NASH, CHC, DILI and SLE patients, as well as in healthy volunteers. Anti‐PCK2 antibody was present in 50.0% (21/42) of AIH, 14.6% (7/48) of PBC, 4.9% (2/41) of NASH, and 10.0% (2/20) of CHC patients, 0% (0/10) of DILI, 12.5% (2/16) of SLE and in 3.3% (1/30) of healthy volunteers. The sensitivity, specificity and accuracy of using the detection of anti‐PCK2 antibody in diagnosing AIH were 50.0%, 91.5% and 83.1%, respectively. None of the AIH patients positive for anti‐PCK2 antibody showed characteristic clinical features. Conclusion Although further investigations into the clinical usefulness are necessary, anti‐PCK2 may have potential as a diagnostic marker for AIH.